Perbandingan Perancangan Sistem Kerja Manual Ball Valve Dan Motor Operated Valve Pada Sistem Peyiraman Pada Pertanian Bayam - Widyantoro, Widyantoro; IR, Anes; AM, Randi (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
water spinach Kale is a nutritious food. The Association of Farmers Groups (GaPokTan) Mekar Jaya Mandiri in Cikupa Village, Karang nunggal, has agricultural land planted with watercress as the main source of income. Watering the water spinach plantations is carried out using a piping system with the distribution of water divided into two groups of blocks which is carried out by adding two ball valve mechanisms as a distribution system. The addition of 2 ball valves created problems for the operator. The work cycle when adding two ball valves is 12 body positions in operating the valve, including walking towards the valve, standing straight, and bending when opening or closing the valve. Walking and bending when opening or closing the ball valve takes a long time. Productivity was increased by developing two ball valves with an automatic valve system called the Motor Operated Valve (MOV). MOV uses an albino program for its operating system, and the operator controls M0V via cell phone. Comparison of work cycles between ball valves and those using MOV. The working time cycles for the redesigned operator open and close the valve is 63 seconds with 12 movements. The longest time is walking towards the valve, which is 16 seconds. After the redesign, the operator only needs a cell phone to operate the valve application so that the movement goes to the valve is 0 seconds, and the work cycle time after the redesign is 6 seconds